GLP-I secretion in healthy and diabetic Wistar rats in response to aqueous extract of Momordica charantia - Gulzar Ahmad Bhat; Haseeb A. Khan; Abdullah S. Alhomida; Poonam Sharma; Rambir Singh; Bilal Ahmad Paray (BMC, 2018)
Abstract Background Diabetes mellitus is one of the major global health disorders increasing at an alarming rate in both developed and developing countries. The objective of this study was to assess the effect of aqueous extract of Momordica charantia (AEMC) on fasting blood glucose (FBG), tissue glycogen, glycosylated haemoglobin, plasma concentrations of insulin and GLP-1 hormone (glucagon-like peptide 1) in healthy and diabetic wistar rats. Methods Male Wistar rats (both normal and diabetic) were treated with AEMC by gavaging (300 mg/kg body wt/day for 28 days). Results AEMC was found to increase tissue glycogen, serum insulin and GLP-1 non-significantly (P > 0.05) in normal, significantly (P < 0.01) in diabetic Wistar rats, whereas decrease in FBG and Glycosylated haemoglobin non-significantly (P > 0.05) in normal, significantly (P < 0.01) in diabetic Wistar rats. The elevation of GLP-1 level in normal and diabetic treated groups may be due to the L-cell regeneration and proliferation by binding with L-cell receptors and makes a conformational change, resulting in the activation of a series of signal transducers. The polar molecules of M. charantia also depolarize the L-cell through elevation of intracellular Ca2+ concentration and which in turn releases GLP-1. GLP-1 in turn elevates beta-cell proliferation and insulin secretion. Conclusion The findings tend to provide a possible explanation for the hypoglycemic action of M. charantia fruit extracts as alternative nutritional therapy in the management and treatment of diabetes.